Characterization of a receptor-like protein for 1,25-dihydroxyvitamin D3 in rat skin. - Simpson, R U (1980)
Isolated rat epidermis possesses a cytosolic 3.5 S receptor-like protein for 1,25-dihydroxyvitamin D3. This 3.5S binder has a high affinity (Kd = 1.4 X 10(-10) M) for 1,25-dihydroxyvitamin D3 and is present in low concentrations (31 fmol of binding sites per mg of cytosol protein). Analog competition for receptor binding revealed the following potency order: 1,25-dihydroxyvitamin D3 > 25-hydroxyvitamin D3 > 1 alpha-hydroxyvitamin D3 > 24 (R),25-dihydroxyvitamin D3 > vitamin D3. The receptor has a molecular weight of 60,000, has affinity for DNA-cellulose, and aggregates in the presence of low potassium concentrations. The 1,25-dihydroxyvitamin D3 binder is stabilized by sodium molybdate (10 mM). Addition of phenylmethylsulfonyl fluoride (3 mM) was found to yield more reproducible receptor preparations. The presence of a 1,25-dihydroxyvitamin D3 binding macromolecule with properties similar to those of the bone and intestinal receptor suggests that skin is an additional target organ for this hormone.